Mass Custimazation for Clothing Industry on An E-Commerce Environment - Ding, Wei (2007)
In the time of the globalization, many industries have changed their operation from old fashion way of mass production. Specialized and customized products have desired increasingly to customers. Wile the internet provides an ideal marketplace for customized, its strategic potential has yet to be fully realized. Mass customization has proposed by many researchers as one of the most favorable strategy to focus on customer requirement. It calls for providing customized products and services to customer on a scale with remaining the benefit of efficiency, productivity, high quality, low costs and rapid response in mass productions.